Analisis Terhadap Tindakan Aborsi Menurut Undang – Undang Nomor 36 Tahun 2009 Tentang Kesehatan - Lu Sudirman; Susilawati Susilawati (Fakultas Hukum, Universitas Internasional Batam, 2014)
Abortion was an act which prohibited in Indonesia. This had been regulated in KUHPidana generally and specificly regulated under Law No. 36 of 2009 About Health. In this Law explained about the legal abortion that caused by raping victim and there was an indication of health problems. However, based on the data from Family Planning Coordination Forum that shown the amount of abortion case reached 2,4 million on 2012. Then, most of that had been done not because the reason of being raping victim and health problems.The purpose of this research is to analyzed the juridical review about abortion case according to the Law No. 36 of 2009 About Health. Then, also analyzed the legality of the abortion action that regulated under that Health Constitution.This research was based on normative law and using comparative law on the appication. The data that had been used was primary data and secondary data, those data then will be proceed and been analyzed, qualitative analysis will be used on the data grouping suitabling with the aspect that will be research. Then, the conclusion that related to this studies wil be explained descriptively.According to the research oucome, we found out that The Law No. 36 Of 2009 About Health already been so detailed regulated about the abortion act that had been legalized. In fact, in Indonesia there were still a lot ilegal abortion case that happened and missused the rule that exist under the Health Law that legalized the abortion on raping case.